ANALISIS KUALITAS PELAYANAN DENGAN MENGGUNAKAN FUZZY SERVQUAL, KUADRAN IPA, DAN INDEKS PGCV - Rosyidah, Hanik; Wuryandari, Triastuti; Rusgiyono, Agus (Jurnal Gaussian, 2015)
Quality of service (service quality) require attention in the field of service. A service is considered and perceived as good if it can meet the customer’s requirement and expectation. This study aims to determine the suitability and student’s expectation of existing services and to determine which services should be prioritized to be improved . The method used is the Servqual gap scores to determine the level of customer satisfaction or provided service based on expectations and performance. The Importance-Performance Analysis’s method and Potential Gain Customer Value (PGCV) to determine the priority of criteria of the service that must be improved. Servqual calculation results indicate a mismatch between perceptions and student’s expectation which is -0,0724. By using IPA quadrant shows that the main indicators for priority services is an indicator of the school environment’s cleanliness. PGCV shows that there are nine indicators of service which becomes the next priorities. Keywords : Service quality, IPA, PGCV, satisfaction, expectation, performance